Social Stratification on This Earth of Mankind by Pramoedya Ananta Toer's Novel - Hesti Miranda (Acitya: Journal of Teaching and Education, 2021)
This Earth of Mankind by Pramoedya Ananta Toer is a historical novel about Dutch colonialism in Indonesia. This paper was aimed to find and describe the social stratification in the past that is written in the This Earth Mankind novel. This paper carried out with only one research question: How is social stratification of This Earth Mankind by Pramoedya Ananta Toer’s Novel?. This paper was qualitative research, specifically in document analysis. The main source of this paper was This Earth of Mankind, the 9th edition publishes by Hasta Mitra in 2002. The total page of this novel was 405. In addition, secondary sources are also needed such as online information about the writer and previous researcher who has been conducted similar research. This paper found that there were three social classes of society in the Dutch era, the Dutch group with privilege, enjoyed the lavish life, and live comfortably. The Native group with privilege, who was born from regent or governor, they can attend education where Dutch and Indo attended to such as E.L.S and H.B.S and the last, native group without privilege, they had low status in the society.